2015
DOI: 10.1631/jzus.b1400184
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in breast cancer: oncogene and tumor suppressors with clinical potential

Abstract: MicroRNAs (miRs) are small single-stranded RNA molecules, which function as key negative regulators of post-transcriptional modulation in almost all biological processes. Abnormal expression of microRNAs has been observed in various types of cancer including breast cancer. Great efforts have been made to identify an association between microRNA expression profiles and breast cancer, and to understand the functional role and molecular mechanism of aberrant-expressed microRNAs. As research progressed, 'oncogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(123 citation statements)
references
References 147 publications
(95 reference statements)
4
114
0
5
Order By: Relevance
“…Our results were in agreement with other prior studies which reported that miR-21 over-expression was associated with tumor grades, higher proliferation index, and lymph node metastasis in BC [5,13,30,76]. Other previous studies showed that miR-21 levels are positively correlated with vascular invasion, visceral metastasis, and advanced clinical stage [13,46,77], and associated with poor response to therapy, and worse survival in BC [49,[78][79][80][81]. Moreover, miR-21 deregulation represented a global cancer phenomenon; associated with poor prognosis and survival in other cancer types including lung cancer [42,82], colorectal carcinoma [54,83], gastric cancer [84], pancreatic cancer [33], diffuse large B-cell lymphoma [36,37].…”
Section: Discussionsupporting
confidence: 92%
“…Our results were in agreement with other prior studies which reported that miR-21 over-expression was associated with tumor grades, higher proliferation index, and lymph node metastasis in BC [5,13,30,76]. Other previous studies showed that miR-21 levels are positively correlated with vascular invasion, visceral metastasis, and advanced clinical stage [13,46,77], and associated with poor response to therapy, and worse survival in BC [49,[78][79][80][81]. Moreover, miR-21 deregulation represented a global cancer phenomenon; associated with poor prognosis and survival in other cancer types including lung cancer [42,82], colorectal carcinoma [54,83], gastric cancer [84], pancreatic cancer [33], diffuse large B-cell lymphoma [36,37].…”
Section: Discussionsupporting
confidence: 92%
“…The expression of genes is regulated, in part, by microRNAs (miRNAs), endogenous small non-coding RNAs (ncRNAs), which play regulatory roles in normal cell function and in diseases, especially cancers, by predominantly binding to cis-elements in the 3ā€² untranslated region of specific mRNAs and regulating their translation or stability [9ā€“13]. Recent studies have begun to elucidate the role of miRNAs in various biological processes, including adipocyte differentiation, metabolic integration, insulin resistance and appetite regulation [14ā€“17].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, the results of the present study demonstrate that miR-106b induces EMT via suppressing the expression of PTEN. Discussion miRNAs, small non-coding RNAs of ~22 nucleotides in length, have been demonstrated to be associated with the occurrence and development of human cancer types where they may function as tumor suppressors or oncogenes (3)(4)(5)(6)20,21). Previous studies have demonstrated the abnormal expression of a number of types of miRNAs in ESCC (22,23).…”
Section: Downregulation Of Pten Partially Increased the Invasion Metmentioning
confidence: 97%